Flexural Fracture Toughness and First-Crack Strength Tests of Steel Fiber-Silica Fume Concrete and Its Engineering Applications - Zhang, J.P.; Liu, L.M.; Zhu, Z.D.; Zhang, F.T.; Cao, J Z. (Проблемы прочности, 2018)
The effect of a steel fiber and silica fume on the first-crack strength and the flexural toughness of concrete is evaluated. The ten sets of specimens with a steel fiber content of 0, 40, 50, and 60 g/m³ and steel fiber types of wave shear and straight shear types with and without a silica fume content of a 10% replacement of the cement weight were tested. The results show that the combined effect of silica fume and steel fiber improve the first-crack load and deflection of specimens to a certain degree and increase the flexural fracture toughness of specimens greatly. In the strengthening effect of steel fiber silica fume concrete, the steel fiber is of first importance, while silica fume is an auxiliary component. The wet steel fiber-silica fume shotcrete support for controlling the surrounding rock mass can provide the whole supporting effect of the anchor mesh shotcrete.